Hydrocephalus and Its Diagnosis - A Review - Ambreen Surti; Ambreen Usmani (Journal of Bahria University Medical and Dental College)
Hydrocephalus is enlargement of the ventricular system of the brain due to increased cerebrospinal fluid (CSF) volume and pressure. Congenital hydrocephalus is further classified as communicating and non-communicating depending on whether there is an obstruction to the flow of CSF or not. Multiple causes have been identified in literature which has been summarized as an imbalance in the production and absorption of CSF. It can lead to cognitive impairment, cerebral palsy and visual field defects. It is crucial to identify this condition prenatally as it can leave a debilitating impact on the fetus. Several modalities like ultrasound, computed tomography scans (CT) and magnetic resonance imaging (MRI) have been used to diagnose hydrocephalus. These can help reduce the disease burden and provide means for timely decisions.